Determination of factors associated with serum cholesterol response to dairy fat consumption in overweight adults: Secondary analysis from an RCT - O'Connor, Aileen; Feeney, Emma L.; Bhargava, Nupur; Noronha, Nessa; Gibney, Eileen R. (Frontiers in Nutrition, 2022)
Physiological and environmental factors can influence inter-individual variance in response to food consumption. Recent evidence exploring the dairy matrix has demonstrated differing effects of dairy fat consumption on serum cholesterol levels when consumed in the form of cheese. However, the extent of this variability and the determinants of response to dairy fat are currently unknown. The objective of this study was to determine the factors associated with lipid metabolism response to a dairy fat intervention, with a focus on serum cholesterol. A 6-week randomised parallel intervention trial was carried out in healthy volunteers aged ≥ 50 y with a BMI ≥ 25 kg/m2. Participants (n=104) consumed 40g (range 39-41) dairy fat daily in addition to their usual diet, in 1 of 3 forms: butter, cheese, or reduced-fat cheese and butter. For the purpose of this analysis, ‘response’ was based on the percentage (%) change in serum total cholesterol (TC), low-density lipoprotein cholesterol (LDL-c), and high-density lipoprotein cholesterol (HDL-c) from pre- to post-intervention. Participants were divided into tertiles (three groups of equal size) for each lipid response. The upper and lower tertiles were used to categorise participants as ‘responders’ and ‘non-responders’. For TC and LDL-c, response was classified as decrease, whereas ‘response’ was defined as an increase for HDL-c. Clinical response was also considered, by calculating pre- and post-intervention prevalence of those meeting target levels of cholesterol recommendations. Participants demonstrating the largest % decrease (tertile 1; ‘responders’) in TC had significantly higher levels of TC and HDL-c, at baseline, and lower levels of triglycerides (TAGs) compared to those in tertile 3 (i.e., TC non-responders). Those with the largest % decrease in LDL-c (tertile 1: LDL-c responders) has higher baseline levels of LDL-c and lower levels of TAGs. Multiple regression analysis revealed that the % change in TC and LDL-c was associated with baseline TC, TAG, body weight and high‐sensitivity C‐reactive protein (hsCRP; P<0.05). Previous work has shown that the dairy food matrix affects lipid response to dairy consumption. This study suggests that phenotypic differences (baseline biochemistry; TC, LDL-c, and TAGs), may also influence response to dairy fat in overweight individuals.